Profil Kemampuan Argumentasi Siswa SMA Pada Pembelajaran Biologi - Bahri, Husnaini; Pallenari, Muhiddin; Ali, Alimuddin (Biology Teaching and Learning, 2021)
Abstract. The ability to argue is one of the 21st century skills that students need to have. The purpose of this study was to determine the scientific argumentation skills of students class XII at the Biringkanaya District High School in answering description questions, especially in the digestive system material. This type of research is a descriptive survey research using purposive sampling technique. The population of this study were students of class XII MIA at State Senior High Schools in Biringkanaya District, Makassar City, South Sulawesi. The sample used in this study is a study group in which students have heterogeneous cognitive abilities. The argumentation ability data is obtained through giving tests. Based on the test results, the overall argumentation skills of students were in the very poor category with a score of 19.74%. The results of the students' arguments showed that in the aspect of making claims with a percentage of 91.4% (very good); aspects include ground with a percentage of 21.64% (less); aspects include backing with a percentage ofÂ  9.88% (very low); aspects include a warranty with a percentage of 5.71% (very low); aspects include qualifier with a percentage of 5% (very low); Â and aspects include rebuttals or reservations with a percentage of 7.3% (very low).Keywords: ability to argument, making claims, rebuttal, reservation, high schools MakassarÂ